The Influence of Information Technology Utilization in Taxation, Tax Socialization, and Tax Sanctions on Individual Taxpayer Compliance at the Bandung Cibeunying Primary Tax Office - Maziyyah Nadhir; Wajib Ginting; Deni Hamdani (CV. Publikasi Indonesia, 2026)
Taxes are a potential source of state revenue to be able to achieve development success, so that from year to year tax revenues are expected to continue to increase in an effort to finance national development. Taxpayer compliance is an important factor in realizing tax revenue targets. The higher the taxpayer's compliance, the more tax revenue will increase, and vice versa. This study aims to test and analyze the influence of information technology in taxation, tax socialization, and tax sanctions on the compliance of individual taxpayers at the Bandung Cibeunying Pratama Tax Service Office. The research method uses explanatory research, a data collection technique using primary data obtained through the distribution of questionnaires. The research sample was 100 respondents, the sampling method used accidental sampling. The data analysis technique used multiple linear regression analysis. The results of the study show that descriptively the application of information technology in taxation, tax socialization, and tax sanctions is optimal, while taxpayer compliance is still low. As for verifiability, the results were obtained that: (1) information technology in taxation has a significant effect on taxpayer compliance, (2) tax socialization has a significant effect on taxpayer compliance, (3) tax sanctions have a significant effect on taxpayer compliance, and (4) information technology in taxation, tax socialization, and tax sanctions have a significant effect on taxpayer compliance.